ANALISIS KETAHANAN PANGAN RUMAH TANGGA PETANI PADI SAWAH DI DESA MONAPA KECAMATAN MOWILA KABUPATEN KONAWE SELATAN - Ariyani, Ni Ketut Hintan; Rosmawaty, Rosmawaty; Zani, Munirwan (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2024)
This study aims to find out (1) How is the food security of paddy rice farming households in Monapa Village, Mowila District, South Konawe Regency; (2) Factors affecting the food security of rice farming households in Monapa Village, Mowila District, South Konawe Regency, with a total sample of 63 respondents using the slovin formula. To answer the first goal using the measurement of the share of food expenditure. For the second purpose using multiple linear analysis. Based on the results of research on the food security of lowland rice farmer households in Monapa Village, Mowila District, South Konawe Regency, the majority of 65.08% of households fall into the food insecure category (share of food expenditure ≥ 60%) and the remaining 34.92% of households included in the category of food security (share of food expenditure ≤ 60%). The factor that has a significant effect on the food security of paddy rice farming households in Monapa Village, Mowila District, South Konawe Regency is household income with a significant value of 0.032 which is less than the value of α (0.05). While the variables of the number of family members, the education of the housewife, the price of rice and eggs have no significant effect on the food security of rice farming households.